(untitled) (Research, Society and Development, 2021)
The paper analyzes judicial cooperation as a procedural management technique for the modification of jurisdiction in order to avoid conflicting decisions. Using the deductive method with doctrinal revision as a methodological option, judicial cooperation is analyzed as a technique capable of giving concrete effect to the principle of efficiency, by modifying competence. As the acts of cooperation, allowing institutional dialogue between judges and bodies of the Judiciary to respond to specific situations, are characterized by the deliberate lack of a rule predefined by the legislator, it is concluded that the acts of cooperation aimed at meeting processes , even though they are authorized by the procedural system, they import in a new form of modification of competence as acts of procedural management that are, to respect the principle of procedural efficiency.